2017
DOI: 10.1007/s00167-017-4791-4
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon elastic properties remain decreased in long term after rupture

Abstract: This study shows that the healed Achilles tendon after rupture has inferior elastic properties even after a long-term healing phase. Differences in elastic properties after rupture mainly originate from the mid-substance of the Achilles tendon, in which most of the ruptures occur. Elastographic results do not correspond with subjective perception. Clinically, sonoelastographical measurements of biomechanical properties can be useful to provide objective insights in tendon recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…As a quantitative tool for evaluating viscoelasticity, US elastography has a potential to improve the diagnosis of tendon disorder . Static elastography has been used to evaluate Achilles tendon viscoelasticity, but this method cannot provide quantitative data and has poor repeatability . Shear wave elastography has been successfully used to evaluate glands and visceral organs as a noninvasive technique .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a quantitative tool for evaluating viscoelasticity, US elastography has a potential to improve the diagnosis of tendon disorder . Static elastography has been used to evaluate Achilles tendon viscoelasticity, but this method cannot provide quantitative data and has poor repeatability . Shear wave elastography has been successfully used to evaluate glands and visceral organs as a noninvasive technique .…”
Section: Discussionmentioning
confidence: 99%
“…5 Static elastography has been used to evaluate Achilles tendon viscoelasticity, but this method cannot provide quantitative data and has poor repeatability. 19,20 Shear wave elastography has been successfully used to evaluate glands and visceral organs as a noninvasive technique. [21][22][23] Previous studies demonstrated that evaluation of the viscoelasticity of tendon using the SWE technique showed good intraoperator and interoperator repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…6,13 There is some data to suggest that plantarflexion strength is never fully restored, even with long-term follow-up. 5,7,10 It remains unclear at this point why an ATR incurs such a long recovery and, further, why strength may not be fully restored. Eliasson et al provided one possibility; these authors placed tantalum beads embedded within the tendon on both sides of the rupture at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Inevitably, tendinopathies lead to tendon rupture and once this happens, tendon natural healing is slow, often poorly responding to treatments and requires prolonged rehabilitation in most cases. Until today, none of the therapeutic options offers satisfactory long-term solutions, meaning that repaired tendons do not regain their complete strength and functionality [5]. However, the understanding of tendon biology, degenerative and healing processes, progresses slowly and the development of new treatment options is therefore insufficient.…”
Section: Terminology Of Tendon Diseasesmentioning
confidence: 99%